Năng lực chuyên biệt của cố vấn học tập hỗ trợ sinh viên học tập tự chủ trong bối cảnh giáo dục đại học hiện nay: Một nghiên cứu tổng quan - Phạm, Thị Thanh Hải; Bùi Phương Thúy (Tạp chí Giáo dục, 2025)
Student autonomy in learning is a key factor in enhancing the quality of higher education. In the current educational context, students are increasingly required to develop self-directed learning and research skills, highlighting the crucial role of academic advisors. To effectively fulfill this role, academic advisors must possess essential competencies, including strong subject-matter expertise, counseling skills, an understanding of student psychology, communication abilities, and the capacity to assess and support students in developing effective self-learning strategies. This paper identifies specific competencies for academic advisors to meet the demands of supporting students in their autonomous learning development at universities. The study aims to provide both theoretical and practical foundations to help universities improve academic advising services, thereby enhancing students’ learning outcomes and overall development.